2017
DOI: 10.2166/wst.2017.642
|View full text |Cite
|
Sign up to set email alerts
|

Removal of antibiotic resistant E. coli in two Norwegian wastewater treatment plants and by nano- and ultra-filtration processes

Abstract: The effectivity of different treatment stages at two large wastewater treatment plants (WWTPs) located in Oslo, Norway, to remove antibiotic resistant Escherichia coli from municipal wastewater was investigated. The WWTPs were effective in reducing the total cultivable E. coli. The E. coli in WWTP samples were mainly resistant to ampicillin (6-27%) and trimethoprim-sulfamethoxazole (5-24%), and, to a lesser extent, tetracycline (3-14%) and ciprofloxacin (0-7%). In the first WWTP, a clear decrease in the percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 11 publications
0
17
1
Order By: Relevance
“…The other way is to remove the microbes by filtration. Nano filtration techniques can also be used for this purpose, which will help to remove the microbes efficiently from water (He et al ., 2018; Schwermer et al ., 2018). A table highlights the properties and advantages of different nanotechnology methods using for water treatment are mentioned in Table 1.…”
Section: Antimicrobial Nanomaterialsmentioning
confidence: 99%
“…The other way is to remove the microbes by filtration. Nano filtration techniques can also be used for this purpose, which will help to remove the microbes efficiently from water (He et al ., 2018; Schwermer et al ., 2018). A table highlights the properties and advantages of different nanotechnology methods using for water treatment are mentioned in Table 1.…”
Section: Antimicrobial Nanomaterialsmentioning
confidence: 99%
“…Research by Kappell et al (2018) has similarly shown the effectiveness of anaerobic MBRs with ARG removals of up to 3.6 log 10 . Schwermer et al (2018) investigated the efficiency of two WWTPs in the removal of ampicillin, sulfamethoxazole, ciprofloxacin, and tetracycline resistant E. coli. The two WWTPs employed a biofilm process and a conventional activated sludge treatment process, respectively.…”
Section: Removal From Wastewatermentioning
confidence: 99%
“… Schwermer et al (2018) investigated the efficiency of two WWTPs in the removal of ampicillin , sulfamethoxazole , ciprofloxacin , and tetracycline resistant E. coli . The two WWTPs employed a biofilm process and a conventional activated sludge treatment process, respectively.…”
Section: Antibiotic Resistance Gene Removal In Wastewater Treatment Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, during therapeutic treatment procedures, the human intestinal microbiota is exposed to high concentrations of antimicrobials that can stimulate the generation of resistance phenotypes before its discharged into sewage through human excreta . Globally, several findings on the presence of antibiotics, as well as the detection of ARB and ARGs in WWTPs final effluents samples have been reported including the study of Schwermer et al (2018). A recent study by Barancheshme and Munir (2018) suggested some strategies to combat antimicrobial resistance (AMR) in WWTPs such as equipment upgrades with new developments, and they also pointed out that urban wastewaters may not ideally undergo appropriate treatment procedures due to broken down facilities in developing countries.…”
Section: Introductionmentioning
confidence: 99%